Batch cultures of Y. lipolytica CBS 2075 on hydrocarbons medium under different conditions of oxygenation - Miranda, Sílvia Cristiana Martins (2023)
Hydrocarbons are hydrophobic pollutants that can be used as a carbon source in microbial-based processes. Yarrowia lipolytica is a nonconventional yeast known for its ability to assimilate hydrophobic substrates to growth and simultaneously produce added-value compounds. The effect of dissolved oxygen concentration on the assimilation of a hydrocarbons mixture, biomass and metabolites production by Y. lipolytica CBS 2075 was studied for the first time. The yeast grew in a mixture of hexadecane, hexadecene, and dodecane, producing enzymes (lipase and protease) and intracellular lipids. Though the amount of dissolved oxygen concentration did not affect Y. lipolytica CBS 2075 cellular growth, the hydrocarbons consumption rate was slightly dependent on the dissolved oxygen concentration. Low amounts of dissolved oxygen concentration had a clear negative effect on lipase production but no differences were found among all dissolved oxygen conditions for lipids and protease production.